2019
DOI: 10.3390/ijerph16081329
|View full text |Cite
|
Sign up to set email alerts
|

Ageism in an Aging Society: The Role of Knowledge, Anxiety about Aging, and Stereotypes in Young People and Adults

Abstract: The progressive aging of society, caused by profound demographic changes, brings with it the necessity of confronting the subject of biases against the elderly. Ageism, in fact, can influence society’s attitudes regarding this population, in addition to impacting the self-perception of elderly people. This, in turn, has consequences for positive outcomes during the aging process. The current research aims to investigate the simultaneous relationships between knowledge, age, anxiety about aging, and stereotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 59 publications
2
71
0
16
Order By: Relevance
“…Negative attitudes and assumptions about older people can influence individual behaviour, social values and norms. Laws protecting against direct or indirect age-based discrimination have to be adopted [38][39][40]. Effort should be made in the media to present a balanced view of ageing, moving away from the conceptualization of older people as a burden and away from unrealistic assumptions that older people today can in some way avoid health challenges on their own without support.…”
Section: Undertaking a Global Campaign To Combat Ageismmentioning
confidence: 99%
“…Negative attitudes and assumptions about older people can influence individual behaviour, social values and norms. Laws protecting against direct or indirect age-based discrimination have to be adopted [38][39][40]. Effort should be made in the media to present a balanced view of ageing, moving away from the conceptualization of older people as a burden and away from unrealistic assumptions that older people today can in some way avoid health challenges on their own without support.…”
Section: Undertaking a Global Campaign To Combat Ageismmentioning
confidence: 99%
“…These ageist stereotypes, prejudice and discrimination are internalized by older adults and act as barriers in the pathways to care. Older adults are far less likely to involve in activism and advocacy for inclusivity and equal rights because of the implicit belief that they must sacrifice their wellbeing and “make way” for the younger generations to replace them ( Cohen, 2001 ; Walsh et al., 2011 ; Donizzetti, 2019 )…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…In particular, third year students had a higher score of ageism than first year students, which can be inferred as the result of increased contact with sick older people in hospital clinical practice. Inconsistent results have been found with respect to the association between age and ageism [ 43 , 44 , 45 ]. Donizzetti [ 45 ] reported a positive correlation between age and ageism, while Kim and Ha [ 16 ] found that age is not associated with ageism.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent results have been found with respect to the association between age and ageism [ 43 , 44 , 45 ]. Donizzetti [ 45 ] reported a positive correlation between age and ageism, while Kim and Ha [ 16 ] found that age is not associated with ageism. Cultural factors that are rapidly increasing the aging population in South Korea could also affect ageism [ 35 ].…”
Section: Discussionmentioning
confidence: 99%